The gel formulation of the aqueous phase of snakehead fish (Channa striata) extract with various combinations of HPMC K4M and Carbopol 934 - Wintari Taurina; Mohamad Andrie; Lea Anjeli (Universitas Ahmad Dahlan, 2018)
Gel is a clear and semi-solid material, translucent and contains active material. The liquid phase of Ekstrak Ikan Gabus contains reactive Albumin benefits to advance the wound-healing process. HPMC and carbopol is the gelling agent uses to form gel material. This research aims to acknowledge the effect of basic combination variety (gelling agent) towards physical and chemical stability of gel material during liquid phase of Ekstrak Ikan Gabus in length of period 28 days. Variety of HPMC: Carbopol used, 25:75%, 50:50%, and 75:25%. Physical and chemical test conducted they are, organoleptic test, dispersion test, bonding strength test and pH test. The result is analyzed through one-way ANOVA and continued by LSD test with validity 95%. The whole formula is resulted a stable physical and chemical during 28 days. The higher the consentration of HPMC the the better its physic and chemistry stability. The best and optimum formula was shown by F3 (75:25%), with a stable organoleptic result during 28 days, homogen, the result of the dispere power weight 50 g (±14,517 cm2) weight 100 g (±16,169 cm2) weight 150 g (±16,957 cm2 ) and the average weight is (±15,881 cm2), the sticky power (±2301,78 second) and pH (±6,42) in which can be considered safe for skin.